SRI indices and responsible corporate behaviour: a study of the FTSE4GOOD index - Slager, Catharina Henrike (2012)
In recent years a large number of rankings, ratings and indices have been developed that attempt to measure the Corporate Social Responsibility (CSR) of companies. Substantive growth in the Socially Responsible Investment (SRI) market in the last decade plays a major role in this development. Little is known about the extent to, and ways in which, the metrics developed for the SRI market may contribute to improvements in CSR. The research aims to answer these questions by studying the FTSE4Good index, an SRI index launched by FTSE Group in 2001. The research examines how this metric for the SRI market is developed by FTSE with the help of third parties; and the influence of the index on the responsible corporate behaviour of included companies. A mixed-methods approach to data collection and analysis is used to study these two research questions, drawing on interviews, archival data and document analysis, media analysis and multivariate analysis.